One hundred benefits mentioned by interpreters from Mosa's marriage story, peace be upon him - Alwadeai, Abdulwahab Abdullah (Journal of Islamic Sciences, 2021)
The main objective of the research: to collect the benefits and lessons that the interpreters mentioned in Mosa's marriage story from all sources.The problem of research was to extract the benefits that the interpreters mentioned in their interpretation books.The research revolves around six Ayah in Surat Al Qasas from Ayah (23) to (28). It amounted to (100) benefits, highlighting the most important results learned from this research.The researcher have followed the historical inductive analytical approach to reach the research objectives.The most important results were, the Mosa's marriage story is a way of life for every male and female believer and there are countless benefits and lessons. The interpreters have gone to great lengths to extract these benefits, and they differ in their capabilities to do so. However, every interpretation book contains features that you will not find in others, and we may find benefits in an abbreviated book that we do not find in an expanded book. The study recommended that researchers continue to collect the benefits and lessons that the interpreters mentioned from Quran stories.
Keywords: hundred; benefits; mosa peace upon him; marriage; interpreters; Surat Al Qasas